Positioning of individual and the mobilisation potential of political discussion networks - Iglič, Hajdeja (Teorija in praksa, 2022)
In the article, we discuss how the political communication and interpersonal influence found in discussion networks add to fragmentation of the political space and the strengthening of political parties at the extremes of the political continuum. To this end, we analyse the mobilisation potential held by discussion networks of people who position themselves on the margins of the left–right political spectrum and compare them with the networks of those positioned in the centre and those who do not align themselves politically. The analysis focuses on four features of discussion networks: size, homogeneity, frequency of political discussion, and frequency of trying to persuade others. The results of the analysis show the most extensive mobilisation potential is found among people in the centre of the political continuum, while people on the far right and far left have networks that are the basis of intense political communication with people holding different political views but lack opportunities for the broad network dissemination of their political views and attitudes
Keywords: Diskusija; diskusijska omrežja; Družbena omrežja; levo-desno; politična orientacija; Politično komuniciranje